Analysis of Clonal Relationships among Shigella spp. Isolated from Children with Shigellosis in Ahvaz, Iran - Bagheri Mohammad Gholi Pour, Maryam; Shokoohizadeh, Leili; Navab-Akbar, Farah Taj (Archives of Advances in Biosciences, 2016)
Shigellosis is one of the important gastrointestinal bacterial infections, particularly among children of developing countries such as Iran. Antibiotic susceptibility pattern and genetic typing for epidemiological purposes are of significant issues in Shigella infectious control. The aim of this study was to investigate the antibiotic susceptibility and genetic relationship among Shigella strains isolated from children with shigellosis at paediatric hospital in Ahvaz, south west of Iran. This study included all Shigella strains isolated from paediatric patients with diarrhea admitted to Abuzar pediatric hospitals in Ahvaz, during January-June 2015. Shigella isolates were identified using standard microbiological and serological methods. Shigella spp strains also were studied by antimicrobial susceptibility testing and Enterobacterial Repetitive Intergenic Consensus (ERIC) - PCR analysis. Total of 50 Shigella strains were isolated from children with dysentery diarrhea. In total, 31 (62%) were identified as Shigella flexneri, 16(32%) and 3 (6%) were Shigella sonnei and Shigella boydii respectively. High level resistance were detected against ampicillin, trimethoprim-sulfamethoxazole and cephalotine. All isolates were sensitive to ceftriaxone, imipenem gentamicin and amikacin. The results of ERIC-PCR data analysis showed 11 different types of Shigella with four closely-related patterns. S. flexneri was the predominant serogroup of Shigella spp. in children in the referral pediatric hospital in Ahvaz. Ampicillin and trimethoprim-sulfamethoxazole is no longer recommended for shigellosis empirical treatment and should be replaced by other antibiotics such as ceftriaxone or ciprofloxcacin. Diverse but genetically close strains of shigella were responsible for shigellosis in paediatric patients in Ahvaz, south west of Iran.